Nature of Crime and Challenges of Policing in Haor Areas of Bangladesh: A Study in Kishoreganj and Netrokona Districts - Miah, Md. Abdul Kader; Shaulin, Nahida (CV. Literasi Indonesia, 2024)
Green criminology is a multidisciplinary field that seeks to explain the relationship between crime and geography. Bangladeshi criminologists and crime preventionists are increasingly conscious of crime-location relationships. This study aims to explore with a new eye the lifestyle of the people of haor areas to find out the root causes of crimes and the challenges of policing in haors areas as well. This study is conducted based on the qualitative approach. The study employed an in-depth interview strategy and focus group discussions (FGDs) to gather information. The findings of the study reveal that the main causes for crime in hoar areas include economic insolvency, lack of education, detached communication system, lack of steady employment, lack of adequate land survey, and pedigree contention within families. The result also shows that the police of hoar areas face difficulties in performing their duties due to poor communication, lack of manpower, political influence, inadequate logistics, and modern weapons. It is essential to study this topic to identify the relationship between geography and crime, which will help to control the crime rate in hoar areas through an effective and modern policing system.